2006
DOI: 10.1159/000089374
|View full text |Cite
|
Sign up to set email alerts
|

Ugandan Kaposi’s Sarcoma-Associated Herpesvirus Phylogeny: Evidence for Cross-Ethnic Transmission of Viral Subtypes

Abstract: Objective: The aim of this study was to test the relationship between Kaposi’s sarcoma-associated herpesvirus (KSHV) phylogeny and host ethnicity at the within-country scale. Methods: KSHV genomic DNA samples were isolated from 31 patients across eleven Ugandan ethnic groups. Amino acid sequences of the ORF-K1 gene were used to construct a neighbor-joining phylogenetic tree. Results: A5 and B1 variants predominated with no evidence of distinct ethnic or geographic distribution. A new K1 subtype (F) was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 80 publications
3
38
2
3
Order By: Relevance
“…Indeed, the prevalence of subtype A5 in Zimbabwe (45%) is remarkably similar to that observed in smaller studies of other ethnic groups in diverse geographic areas in Africa: A5 was identified in 53% of 31 KS patients in Uganda (Kajumbula et al 2006) and 34% of 32 KS patients in West and Central African countries (Lacoste et al 2000). Zimbabwean A5 sequences in our study were closely related to each other and to reference sequences from distant areas of Africa with little evidence of genetic diversity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, the prevalence of subtype A5 in Zimbabwe (45%) is remarkably similar to that observed in smaller studies of other ethnic groups in diverse geographic areas in Africa: A5 was identified in 53% of 31 KS patients in Uganda (Kajumbula et al 2006) and 34% of 32 KS patients in West and Central African countries (Lacoste et al 2000). Zimbabwean A5 sequences in our study were closely related to each other and to reference sequences from distant areas of Africa with little evidence of genetic diversity.…”
Section: Discussionsupporting
confidence: 86%
“…One hypothesis to explain the distribution of K1 subtype A5 in Africa is that a prototype A5 gene was introduced into African populations through a "very rapid and recent aggressive spread" augmented by a selective advantage of the A5 allele (Hayward and Zong, 2006). Indeed, the prevalence of subtype A5 in Zimbabwe (45%) is remarkably similar to that observed in smaller studies of other ethnic groups in diverse geographic areas in Africa: A5 was identified in 53% of 31 KS patients in Uganda (Kajumbula et al 2006) and 34% of 32 KS patients in West and Central African countries (Lacoste et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional peripheral blood mononuclear cell (PBMC) samples collected anonymously with consent for diagnostic and research analysis from KS patients at the University of Kampala in Uganda (HKS6 to HKS67 set) were also reported on previously for ORF-K1 (Kajumbula, 2006). A series of KS biopsy DNA samples from the Republic of South Africa (SAKS21 to SAKS35 set) were provided by Lee Alagiouzoglou, Lynn Morris and Fred Sitas (National Virology Institute, Johannesberg).…”
Section: Source Of Dna Samplesmentioning
confidence: 99%
“…Nevertheless, some genomes that are identical in ORF26 differ at other loci, and linkage and recombination patterns across the entire KSHV genome can be complex. Furthermore, when all eight constant region loci plus the VIP (K1) and TMP (K15) genes are all taken into account, very few African genomes fail to show at least some chimerism Kajumbula, et al, 2006;Zong, et al, 2002). The situation is much simpler for Eurasian genomes, with only 30 to 50% showing one or more inter-subtype recombination events (Zong, et al, 2002).…”
Section: Linkage and Recombination Between Multiple Genomic Locimentioning
confidence: 99%